2012
DOI: 10.1007/978-3-642-33475-7_13
|View full text |Cite
|
Sign up to set email alerts
|

On Union-Free and Deterministic Union-Free Languages

Abstract: Abstract. The paper continues the study of union-free and deterministic union-free languages. In contrast with the fact that every regular language can be described as a finite union of union-free languages, we show that the finite unions of deterministic union-free languages define a proper subfamily of regular languages. Then we examine the properties of this subfamily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…As new subregular classes of languages, we may consider the finite unions of deterministic union-free languages [8].…”
Section: N-wordsmentioning
confidence: 99%
See 2 more Smart Citations
“…As new subregular classes of languages, we may consider the finite unions of deterministic union-free languages [8].…”
Section: N-wordsmentioning
confidence: 99%
“…Later on, in [4], their description by equations were examined, and it was shown that this class cannot be axiomatized by a finite set of equations. Automata theoretical characterisation was given in [11] allowing to define the deterministic counterpart of the class, the family of deterministic union-free languages [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown in [15] that the class of languages defined by DFAs with the one-cycle-free-path property is a proper subclass of that defined by one-cycle-free-path NFAs; the former class is called the class of deterministic union-free languages. In 2012 Jirásková and Nagy [16] proved that the class of finite unions of deterministic union-free languages is a proper subclass of the class of regular languages. They also showed that every deterministic union-free language is accepted by a special kind of a one-cycle-free-path DFA called a balloon DFA.…”
Section: Introductionmentioning
confidence: 99%